2018
DOI: 10.1136/sextrans-2018-053592
|View full text |Cite
|
Sign up to set email alerts
|

Increasing HIV testing engagement through provision of home HIV self-testing kits for patients who decline testing in the emergency department: a pilot randomisation study

Abstract: NCT03021005, results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Fifth, we assume that among high-risk individuals, risk disclosure is accompanied by an HIV test being offered and accepted, whereas likely there is some attrition for both steps. Sixth, we could not include a role for self-testing, a relatively new technology which in clinical trials shows impressive potential to increase testing and detection of infections 47,48 but for which we could find no use statistics.…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, we assume that among high-risk individuals, risk disclosure is accompanied by an HIV test being offered and accepted, whereas likely there is some attrition for both steps. Sixth, we could not include a role for self-testing, a relatively new technology which in clinical trials shows impressive potential to increase testing and detection of infections 47,48 but for which we could find no use statistics.…”
Section: Discussionmentioning
confidence: 99%
“…A small, randomised study in the USA of emergency department attendees who declined an HIV test demonstrated higher subsequent HIV testing among individuals provided with an HIV self-test kit compared with those who were only offered advice [44].…”
Section: Self-testingmentioning
confidence: 99%
“…With PrEP referrals reliant on first obtaining a negative HIV test, the inability to access commonly used in-person HIV testing services makes initiating PrEP more difficult. PrEP use is recommended for HIV-negative individuals who engage in higher-risk sexual activity, as it significantly decreases their risk of contracting HIV [ 41 ]. Most PrEP referrals are provided during an in-person HIV testing appointment by the test counselor or prescribed by a physician during a medical visit.…”
Section: Linkage To Prepmentioning
confidence: 99%